Modifikasi sodium lignosulfonat melalui epoksidasi minyak biji kapuk dan penambahan kosurfaktan - Muhammad Khoirul Anam; Suryo Purwono; Supranto Supranto (Jurnal Rekayasa Proses, 2015)
The objective of this research is to reduce the interfacial tension of sodium lignosulfonate (SLS). SLS formulation (1%) showed the interfacial tension of 2.34 mN/m. This value is still relatively large when compared to interfacial tention of required surfactant for enhanced oil recovery (EOR). The terms of surfactants that can be used in EOR must have ≤10-3 mN/m interfacial tension. The performance of SLS was expected to be improved by adding the epoxide compound and co-surfactants (1-octanol). Epoxide compound was made by reacting kapok oil with acetic acid and hydrogen peroxide with in-situ method. Temperature of epoxidation reaction was varied i.e. 60°C, 70°C and 80°C, while the time of reaction was varied from 15 to 90 minutes. The evaluation showed that equation of the reaction rate coefficient (k) for the epoxide was ????= 124,82 exp (−24,14/RT). The addition of the epoxide compound 0.5% w/w of the formulation SLS was able to reduce the interfacial tension value up to 9.95 x 10-2 mN/m. The addition of co-surfactant (1-oktanol) was varied between 0.1 and 0.4% of the total mass (SLS + epoxide + water formation). The lowest interfacial tension (2.43 x 10-3 mN/m) was obtained by co-surfactants addition of 0.2% w/w.